The use of the periodical collection at the University of the Philippines Los Baños Main Library its implications to serials collection development - Mallion, Editha A.; Esquejo, Nemesio A.; Zamora, Milagros C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1992)
The study was conducted to obtain data which to identify the most frequently used periodical titles, to determine which periodical titles need to be cancelled, retained or acquired and to formulate a periodical selection policy that will serve as basis in coming up with a collection development program at the UPLB Main Library. A survey was conducted randomly in UPLB Main Library by choosing every fifth user of the periodical collections in a day from September 11, 1991 to December 11, 1991. Respondents were composed of 357 students, 80 faculty and 55 researchers totaling to 492.
Most of the respondents used the periodical collection to keep them abreast with the latest information in their respective fields. Also, majority of the respondents expressed satisfaction in the information sources. Seven hundred thirty-eight titles were extensively used by the respondents during the school year 1991-1992. Some respondents suggested titles which need to be cancelled, and these are: Computer and People, Consumer Reports and Farmers' Weekly. Periodical titles on Computer Science should be given attention. Results of the study revealed that a total of fifty-eight titles which are needed by the users are not available. It was also suggested that titles received on exchange basis and as gifts should be maintained, particularly those related to instruction and research.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Periodicals -- Circulation; Periodicals -- Use studies; University of the Philippines Los Baños -- Main Library